Measuring Harmonic Mixer in the Frequency Range from 78.33 to 118.10 GHz - I. A. Zakharov; A. V. Gusinsky; A. V. Saikov; M. M. Kasperovich; D. A. Kondrashov; M. S. Svirid (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2024)
The issues of realization of ultra-high-frequency measuring mixers on harmonics with a built-in frequency diplexer and the relevance of their application are considered. A mathematical model of a measuring harmonic mixer of the millimeter-wave range as a linear device is described. A functional diagram and technical characteristics of a measuring harmonic mixer with a built-in frequency diplexer are given. The results of computer modeling of the module of the diplexer transmission coefficient by the high-frequency input and low-frequency output, as well as the standing wave ratio by the voltage of the measuring channel of the harmonic mixer in the frequency range from 78.33 to 118.10 GHz are shown. The implementation of the developed mixer in this frequency range is presented.